Estrada, O. (ed) (2023). "Rosa Beltrán: afectos literarios y el arte de narrar". Bonilla Artigas Editores. - Israel Perez Medina (América sin Nombre, 2025)
Reseña del libro Estrada, O. (ed) (2023). "Rosa Beltrán: afectos literarios y el arte de narrar". Bonilla Artigas Editores. 362 pp. ISBN: 9786078838981.